Evaluation of the Perth Bike to Work Breakfast - McManus, Alexandra; Smith, Jennifer; McManus, Jennifer; MacDonald, E.; Williams, M. (Public Health Association of Australia, 2005)
Perth Western Australia, has the highest proportion of per capita car ownership in Australia. Despite the various health, environmental and traffic-related benefits, the uptake of alternative forms of transportation such as walking, cycling and public transport are low. In response to a growing reliance on motorised transport, the Department for Planning and Infrastructure’s Cycling Unit conducts an annual Bike to Work Breakfast to promote cycling as a viable form of transport to work. This initiative has been evaluated over the past five years with results demonstrating positive trends in attitudes and behaviours towards cycling- related issues. This paper will discuss the findings from 1657 respondents who participated in the 2004 Bike to Work Breakfast and will investigate trends over the past five years for cycling-related attitudes and behaviours amongst the Perth population.